(3ChQGb fOhI hhQTI Yed GdGSGdjH GdMOjKI aj GdGOGQI GdeGdjI GdYGeI GdefYbO HGdbGgQI aj SHJeHQ (B2006s ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B,s, 2007)
(3fMhi JWHjb ehGRfI GdGOGA dJMbjb GdGOGQI GdQTjOI aj GdOhdI GdYQHjI , eONd JMdjdj dLOhi GdeTQhYGJ GdYGeI aj GdbWGY GdMchej , CSGdjH EOGQI GdeGdjI GdYhejI HJhfS bWGY GdJYdje GdYGdj fehPLG , eONd ebJQM dJYXje bjeI GdGSJKeGQ GdCLfHj GdeHGTQ HGdYGde GdYQHj , eONd Jbjje GdeTQhYGJ , GdJfXje GdeMGSHj dGOGQI GdOjf GdYGe GdeMdj dCZQGV QaY GdcaGAI GdGOGQI GdeGdjI , cjajI JhGRf GdgjGcd GdeGdjI aj GdbWGY GdMchej s
Keywords: (3GOGQIs; (3GdGOGQI GdeGdjIs; (3GdSjGSI GdeGdjIs; (3eGdjI YGeIs